Hibiscus sabdariffa L. leaves as an alternative source of bioactive compounds obtained through high pressure technologies - Clímaco, Gabrielli Nunes (2023)
The aim of the present study was to obtain bioactive compounds from hibiscus leaves through supercritical fluid extraction (SFE) and pressurized liquid extraction (PLE). For SFE, temperature, pressure, and co-solvent were evaluated on extraction yield (X0), content of bioactive compounds and antioxidant activity (AA). For PLE, temperature and solvent composition were evaluated on the same responses. The highest X0 was observed at 60 °C, 300bar and 15% of co-solvent for SFE, and at 100 °C and ethanol 75% for PLE. For bioactive compounds, different results were observed. For SFE, the best condition was at 60 ºC, 100bar and 15% of co-solvent, and for PLE at 80 ºC with ethanol 99.5%. Regarding AA, SFE extracts presented highest values at 60 ºC, 100bar and 5% of co-solvent while PLE presented better results at 60 °C and 99.5%. Chlorogenic acid and quercetin were the main compounds identified in the extracts.